Pengaruh Gaya Kepemimpinan Situasional Asisten Afdeling Terhadap Kinerja Implikasinya Terhadap Produktivitas Kebun Kelapa Sawit Labuhanbatu I Dan Labuhanbatu II PI Perkebunan Nusantara III - Rajagukguk, Albiden; Lubis, Yusniar; Syaifuddin, Syaifuddin (Universitas Medan Area, 2021)
Work productivity increases when the appropriate leadership style is applied. The use of a situational leadership style must remark to the maturity level of followers, as the proper treatment of followers will assist in targets achievement optimally, whereas the failure of leaders in managing resources causing minimal results. This study aims to determine the effect of leadership style on performance and its implications for the achievement of work productivity, to determine the differences in the application of leadership styles and their effects on productivity, and how situational leadership styles are applied to the readiness level of followers. Primary data were gained using a survey method by distributing questionnaires to research respondents. Respondents were all Mandor I and Mandor Panen in District Labuhanbatu I and District Labuhanbatu II. The sampling technique is purposive sampling with the specific criteria, such as that the employees have worked for at least 10 years and have occupied strata III and II positions which are directly related to production excavation. The hypothesis is tested by simple regression and using the RSSM questionnaire calculation. The results of the analysis explain that leadership style has a positive effect on performance and has an impact on productivity, the leadership style of the two Districts is relatively the same, the application of the leadership style is adjusted to the level of readiness of followers, and the production results of the two Districts are not significantly different. The main implication of this research is as to provide the consideration for Board of Management in conducting training to increase the level of ability (competence) and willingness (motivation and commitment), especially for followers and leader levels which are still low.